Game analysis and clinical use of the Xbox-Kinect for stroke rehabilitation. Issue 4 (December 2018) - Givon Schaham, Noa; Zeilig, Gabi; Weingarden, Harold; Rand, Debbie
Abstract : Whole-body movement is required to interact (play) with Microsoft Xbox with the 3D Kinect sensor (Xbox-Kinect) and, therefore, may be suitable for encouraging and practicing movements as part of stroke rehabilitation. We aimed to describe (i) game analysis, (ii) clinical use, and (iii) to characterize the Xbox-Kinect game experience with individuals with chronic stroke. Four therapists played the Xbox-Kinect games and then carried out a games analysis on the basis of the categories suggested by Deutsch. Eleven participants (age 29–69 years) with chronic stroke and varying motor deficits played Xbox-Kinect games for 4–22 sessions as part of a video-game group intervention and the clinical use was documented. The game experience of 'Bowling' (Kinect-Sport) and '20 000 leaks' (Kinect Adventures) was characterized by self-report questionnaires. Detailed tables of game analysis are provided. The clinical use of the console with the participants is presented. Participants reported high enjoyment and 'somewhat-high' perceived exertion after playing the two games and stated that overall the console suited their therapeutic goals. This information can assist clinicians with their clinical reasoning and decision-making for incorporating the Xbox-Kinect into stroke rehabilitation. Potentially, the Xbox-Kinect could be used as an on-going tool to facilitate whole-body movement and physical activity of individuals with chronic stroke.